2020
DOI: 10.1007/s00338-020-01938-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental flexibility in Oulastrea crispata in a highly urbanised environment: a microbial perspective

Abstract: Increasing temperatures on a global scale and locally deteriorating water quality affect coral distribution and health. Mechanisms that convey environmental robustness are poorly understood and have been attributed to the coral host, algal symbionts, and prokaryotic associates. Flexibility of the host’s (bacterial) microbiome has been suggested to contribute to environmental robustness, but the underlying mechanisms are unclear. We therefore utilised the vastly contrasting water quality gradient present along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This suggests that this gorgonian is in the ‘microbiome regulator’ spectrum, as its microbiome is relatively stable but exhibits some variation, mostly in the abundances of core microbes. We also observed stability in the structural complexity of the microbiome of E. cavolini (based on alpha diversity metrics), which has been linked to tolerance of another coral in the ‘microbiome regulator’ spectrum to environmental change ( Röthig et al, 2020 ). As all colonies of A. subpinnata sampled were visually healthy, the differences in the microbiota among populations and time points likely did not reflect an unhealthy state of the holobiont or a pathobiome.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that this gorgonian is in the ‘microbiome regulator’ spectrum, as its microbiome is relatively stable but exhibits some variation, mostly in the abundances of core microbes. We also observed stability in the structural complexity of the microbiome of E. cavolini (based on alpha diversity metrics), which has been linked to tolerance of another coral in the ‘microbiome regulator’ spectrum to environmental change ( Röthig et al, 2020 ). As all colonies of A. subpinnata sampled were visually healthy, the differences in the microbiota among populations and time points likely did not reflect an unhealthy state of the holobiont or a pathobiome.…”
Section: Discussionmentioning
confidence: 81%
“…Briefly, each C. xamachana sample hosts between 51 and 300 distinct OTUs which is in the same range (~100) as the cnidarian anemones E. pallida [73] and Hydra vulgaris [76] (Additional File 3: Table S6). In coral, the numbers are more variable depending on species and environmental conditions, but are generally at the order of tens to hundreds of OTUs [71,77,78]. Considering the best blastn hits for each OTU, we found that 9 of the 15 core microbiome member OTUs have previously been identified in corals and five in E. pallida (Additional File 3: Table S7).…”
Section: The Associated Bacterial Microbiome Shares Characteristics Wmentioning
confidence: 97%
“…Despite dramatic differences in environmental conditions among reefs, O. crispata's microbiome was relatively stable, even at sites with very poor water quality. These results suggest that O. crispata maintains a conserved microbiome, and that environmental flexibility in its bacterial complement does not underpin robustness of the coral, but rather its wide environmental tolerance may be largely due to acclamatory or adaptive mechanisms in the coral host itself (Röthig et al 2020). These findings are in contrast to the findings of Wainwright et al (2019) who examined the bacterial communities of Pocillopora acuta across the urbanized reef environment of Singapore.…”
Section: Urban Reefsmentioning
confidence: 98%
“…Flexible host-bacterial associations have been suggested to provide opportunity for dynamic microbiome adjustment under environmental change (Ziegler et al 2019), permitting corals to optimize their bacterial compliment to reflect prevailing conditions and enhance survival. Röthig et al (2020) tested this hypothesis by examining the microbiome of Oulastrea crispata across the water quality gradient presented by Hong Kong's highly urbanized coastline. Despite dramatic differences in environmental conditions among reefs, O. crispata's microbiome was relatively stable, even at sites with very poor water quality.…”
Section: Urban Reefsmentioning
confidence: 99%